دور رأس المال الاستثماري في تمويل المؤسسات الناشئة (دراسة حالة شركة Finalep) - فرحات كلثوم; نعروره علي; مصطفاوي مبروكة شافية (جامعة الوادي University Of Eloued, 2024)
The study aims to explore the role of venture capital in financing startups, as financing is one of the fundamental aspects in establishing, operating, and expanding startups, whether small or medium-sized. The study focuses on meeting the financial needs of these institutions to enable them to engage in their activities and ensure their continuity in the market. Therefore, the development of financing tools is of great importance to financiers and investors. The Algerian-European Financial Contribution Company (FINALEP) was selected to study the activity of venture capital in Algeria, with the company's activity being studied using a descriptive approach. The study has yielded several results, including the positive impact of the financing techniques used by FINALEP on startups. In addition to providing financing operations with substantial budgets, the company also offers consultancy and monitoring services to startups through its activities in financial engineering.
The role of venture capital in financing startups (a case study of FINALEP)
Keywords: رأس المال الاستثماري; مؤسسة ناشئة; رأس مال التنمية; رأس مال المخاطر; FINALEP; Venture Capital; start-up; development capital; risk capita